The Long-Term Effectiveness of Interventions Addressing Mental Health Literacy and Stigma of Mental Illness in Children and Adolescents: Systematic Review and Meta-Analysis - Alexandra Maria Freţian; Alexandra Maria Freţian; Patricia Graf; Sandra Kirchhoff; Gloria Glinphratum; Torsten M. Bollweg; Odile Sauzet; Ullrich Bauer (Frontiers Media S.A., 2021)
Objectives: This study aims to provide a systematic review and meta-analysis of the literature on the long-term effects of interventions addressing children's and adolescents' mental health literacy and/or stigmatizing attitudes.Methods: Articles in English or German published between January 1997 and May 2020 were retrieved from five databases, leading to a total of 4,375 original articles identified.Results: 25 studies were included after applying exclusion criteria, 13 of which were eligible for meta-analysis. The overall average of the follow-up period was about 5 months. Long-term improvements were sustained for mental health literacy, d = 0.48, 95% CI = (0.34, 0.62), as well as for stigmatizing attitudes, d = 0.30, 95% CI = (0.24, 0.36), and social distance, d = 0.16, 95% CI = (0.03, 0.29). The combination of educational and contact components within interventions led to worse results for mental health literacy, but not stigmatizing attitudes or social distance.Conclusion: Interventions targeting children and adolescents generally have a brief follow-up period of an average of 5 months. They show a stable improvement in mental health literacy, but are to a lesser degree able to destigmatize mental illness or improve social distance.